Kemampuan Pemecahan Masalah Matematis Berdasarkan Motivasi Belajar pada Discovery Learning Berbantuan Lumio by Smart - Anik Setyaningsih; Amidi Amidi (MAN 4 Kota Pekanbaru, 2026)
Mathematical problem-solving ability is one of the main focuses of 21st-century education. This research aims to examine the effectiveness of the Discovery Learning model assisted by Lumio by Smart on students’ mathematical problem-solving ability and to describe students’ problem-solving ability in terms of learning motivation. This study employed a mixed-methods approach with an explanatory sequential design. The research population is all students of class XI of MAN Temanggung. Quantitative data were obtained from randomly selected students, while six qualitative subjects were chosen purposively based on their levels of learning motivation. Research instruments included a mathematical problem-solving test, a learning motivation questionnaire, and interviews. The results indicate that the Discovery Learning model assisted by Lumio by Smart is effective in improving students’ mathematical problem-solving ability. Furthermore, students’ mathematical problem-solving ability varies according to their level of learning motivation, with highly motivated students showing good ability, moderately motivated students showing sufficient ability, and low-motivation students showing low ability.